Cognitive trajectories over 4 years among HIV-infected women with optimal viral suppression. (10th October 2017) - Rubin, Leah H.; Maki, Pauline M.; Springer, Gayle; Benning, Lorie; Anastos, Kathryn; Gustafson, Deborah; Villacres, Maria C.; Jiang, Xiong; Adimora, Adaora A.; Waldrop-Valverde, Drenna; Vance, David E.; Bolivar, Hector; et al.
Abstract : Objective: To determine whether persistent viral suppression alters cognitive trajectories among HIV-infected (HIV+) women on combination antiretroviral therapy (cART) by investigating performance longitudinally in uninfected (HIV−) and 3 groups of HIV+ women: those with consistent viral suppression after continuous cART use (VS), those without consistent virologic suppression despite continuous cART use (NVS), and those without consistent virologic suppression after intermittent cART use (Int NVS). Methods: Two hundred thirty-nine VS, 220 NVS, 172 Int NVS, and 301 HIV− women from the Women's Interagency HIV Study (WIHS) completed neuropsychological testing every 2 years for 3 visits between 2009 and 2013. Mixed-effects regressions were used to examine group differences on continuous T scores and categorical measures of impairment (T score <40). Results: On global function, VS women demonstrated lower scores and were more likely to score in the impaired range than HIV− women ( p = 0.01). These differences persisted over time (group × time, p > 0.39). VS women demonstrated lower learning and memory scores than HIV− women ( p < 0.05) and lower attention/working memory and fluency scores than HIV− and NVS women ( p < 0.05). Group differences in scores persisted over time. Categorically, VS women were more likely to be impaired on attention/working memory and executive function than HIV− women ( p < 0.05). On motor skills, VS and NVS women showed a greater decline and were more likely to be impaired than HIV− women ( p < 0.05). Conclusions: Cognitive difficulties remain among HIV+ women despite persistent viral suppression. In some instances, VS women are worse than NVS women, reinforcing the need for novel adjunctive therapies to attenuate cognitive problems.